The Role of Leadership in the Creation and Planning of Pacification Police Units (UPPs) in Rio de Janeiro - Moraes, Joysi; Mariano, Sandra R.H.; Franco, Andréa Marinho de Souza (Revista de Administração da UFSM, 2017)
The Pacification Police Units (UPPs), created to recover territories (favelas) dominated by drug traffickers in the city of Rio de Janeiro, came about as a result of the courage and leadership of the head of Public Security Bureau in the State of Rio de Janeiro. The UPPs were created at the initiative of a public administrator and, initially, without the support of the State, and have since become one of the most respected and widely recognized organizations in Brazilian society. Due to the success at dismantling the gangs that controlled the favelas and constituted a parallel state within them, UPPs have become the center of a public policy that has allowed their deployment in other underserved communities. In turn, this has enabled the installation of other public services and facilities such as schools and health centers in the favelas, as well as creating the conditions for the local population to freely come and go. Therefore, the purpose of this article is to analyze the role of leadership in the creation and planning of the UPPs distributed among the favelas of Rio de Janeiro. In preparing this article, emphasis has been given to the use of oral history, a methodology that focuses on the history of the present through the narrative of the subjects who participated in the events. The Situational Strategic Planning and the Freirean perspective were used for analysis. The story of the UPPs was found to revolve around the existence or not of leaders inside and outside the favelas. Even with 37 UPPs already installed in the city of Rio de Janeiro, each one being the result of a different experience with the communities, the role of the leaders in the favelas is still emphasized.